Identification of Trypanosoma cruzi Discrete Typing Units (DTUs) through the implementation of a High-Resolution Melting (HRM) genotyping assay (2013)
Background Chagas disease, caused by Trypanosoma cruzi, is a geographically widespread anthropozoonosis that is considered a major public health problem in Latin America. Because this parasite presents high genetic variability, a nomenclature has been adopted to classify the parasite into six discrete typing units (DTUs): TcI, TcII, TcIII, TcIV, TcV, and TcVI, which present different eco-epidemiological, clinical, and geographic associations. Currently, the available genotyping methods present a series of drawbacks that implies the need for developing new methods for characterizing T. cruzi DTU’s. The aim of this work was to genotype reference populations from T. cruzi by means of a High-Resolution Melting (HRM) genotyping assay. To genotype the DTUs of 38 strains and 14 reference clones of T. cruzi from diverse sources, real-time PCR (qPCR) was coupled to high-resolution melting (HRM) based on the amplification of two molecular markers—the divergent domain of the 24 s? rRNA gene and the intergenic region of the mini-exon gene. Findings Amplification of the mini-exon gene allowed the genotyping of three distinct groups: TcI, TcII- TcIV- TcV, and TcIII-TcVI, while amplification of the 24s? gene generated non-overlapping melting temperature ranges for each DTU that were used to identify the groups in the six existing DTUs of Trypanosoma cruzi. Conclusions The proposed genotyping assay allowed discrimination of the six genetic groups by obtaining specific melting curves for each DTU. The application of this technique is proposed because of its specificity, sensitivity, high performance, and low cost compared with other previously described characterization methods.